1969
DOI: 10.1182/blood.v34.6.791.791
|View full text |Cite
|
Sign up to set email alerts
|

On the Development of Slowly-turning-over Cell Types in Neonatal Rat Bone Marrow (Studies Utilizing the Complete Tritiated Thymidine Labeling Method Complemented by C-14 Thymidine Administration)

Abstract: 1. The continuous H3-thymidine (H3-TdR) intravenous infusion of rats from day 9 of pregnancy until term results in the labeling of every single cell nucleus in the body of the offspring. Completely labeled newborn rats were sacrificed at serial intervals after birth. This provided the opportunity to follow the labeling pattern of all bone marrow cells during the development of this organ. Cytokinetically three types of cell renewal systems could be found: one type showed a rapid turnover losing all H3-TdR with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This population of marrow small lymphocytes is itself probably heterogeneous both functionally and kinetically. In young rats, following prenatal and neonatal exposure to 3H-thymidine, Haas et al (1969) have described a persisting population of small lymphocytes within the marrow. These cells showed changes during marrow stimulation suggesting a resting stem cell function (Haas, Bohne & Fliedner, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…This population of marrow small lymphocytes is itself probably heterogeneous both functionally and kinetically. In young rats, following prenatal and neonatal exposure to 3H-thymidine, Haas et al (1969) have described a persisting population of small lymphocytes within the marrow. These cells showed changes during marrow stimulation suggesting a resting stem cell function (Haas, Bohne & Fliedner, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies of bone regeneration identified the presence of nonhematopoietic, label‐retaining cells within bone marrow, suggesting the presence of quiescent MSCs capable of responding to bone injury and contributing to bone regeneration. For example, label‐retaining MSCs were detected within bone marrow after injecting 3 H‐TdR label in rat, from day 9 of pregnancy till birth . In addition, label‐retaining MSCs within murine bone marrow could be enriched by 5‐FU treatment .…”
Section: Analysis Of Quiescence In Ascsmentioning
confidence: 99%
“…The marrow macrophage is a differentiated cell of the mononuclear phagocyte series (13) that does not divide (6,7), so the observed rapid multiplication of M. lepraemurium does not seem to be connected with the multiplication of the host cell. Possibly some breakdown product of the cell debris of the marrow provides a necessary nutrient.…”
Section: Discussionmentioning
confidence: 99%
“…Mice of highly susceptible strains (e.g., CBA, BALB/c) infected intravenously with 10" Mycobacterium lepraemurium develop a progressive disease that kills them in 5 to 6 months. The overall generation time of the bacteria in such animals is 7 to 10 days (17), but Brown and Krenzien (2; Int. J. Lepr.…”
mentioning
confidence: 99%